2014
DOI: 10.1111/1460-6984.12100
|View full text |Cite
|
Sign up to set email alerts
|

Language development of children born following intracytoplasmic sperm injection (ICSI) combined with assisted oocyte activation (AOA)

Abstract: This study presents the first data concerning language outcome in 3-10-year-old children born following AOA. General language scores of the AOA children in this study are located within the normal ranges. The language development of singletons was significantly better compared with twins. Although the results are reassuring for language development, in future long-term follow-up studies in this population are necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 27 publications
3
11
0
Order By: Relevance
“…Until now, the few studies on the outcome of children born after the use of calcium ionophore report neonatal and neurodevelopmental outcomes within the normal range [8,9]. Miller et al [10] reported six birth defects in 62 (9.6%) children born after oocyte activation with ionophore A23187 (calcimycin), but this number was not statistically different from the 6.1% (26/426) children after ICSI without oocyte activation in their study.…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…Until now, the few studies on the outcome of children born after the use of calcium ionophore report neonatal and neurodevelopmental outcomes within the normal range [8,9]. Miller et al [10] reported six birth defects in 62 (9.6%) children born after oocyte activation with ionophore A23187 (calcimycin), but this number was not statistically different from the 6.1% (26/426) children after ICSI without oocyte activation in their study.…”
Section: Introductionmentioning
confidence: 72%
“…Firstly, due to its specific indication, the number of patients that may benefit from this technique is rather small, leading to a low number of children born after transfer of an embryo obtained after oocyte activation. While we described the medical outcome of 47 children conceived at our center, only two other reports on medical follow-up of children born after AOA are available in literature, both from the same group [8,9]. Obviously, the described number of children should be much higher in order to draw firm conclusions regarding the safety of AOA for the offspring, particularly regarding congenital malformations.…”
Section: Discussionmentioning
confidence: 99%
“…Neonatal and sociodemographic data were collected using a parental questionnaire [18]. To measure language development, the CELF was used.…”
Section: Methodsmentioning
confidence: 99%
“…Additional measures are required when carrying ICSI for these couples. To overcome this inadequacy, AOA can be implemented but there is also an increasing requirement to avoid unnecessary AOA as the long term effects of these procedures need to be evaluated, despite several studies emphasizing safety of this procedure [Deemeh et al 2015;D'haeseleer et al 2014;Vanden Meerschaut et al 2014]. Therefore, certain criteria are required to select the correct candidate for AOA.…”
Section: Discussionmentioning
confidence: 99%